CTS e a modelagem matemática na formação de professores de física - MOUTINHO, Pedro Estevão da Conceição (Universidade Federal do Pará, 2012)
This study is about a research among research-teacher, physics teacher and his class of licenciatura in the Centro Federal de Educação Tecnológica do Pará - CEFETPA, composed of 32 students in witch was used CTS Trend and the Mathematical Modeling as environment for formation of physics teachers. It is about participant research, in the modality narrative, with objective to register and analyze the actions and the register of the characters of the research. Six activities with the objective of collect data to answer the problem proposal in this investigation were planned. These data had been registered trough film, writing from the students and writing from the research-teacher. In the analyzes of the results, it is conclude of the environment proportionate by the CTS Trend and by Mathematical Modeling, trough the experimentation, are necessary for formation of a differentiated teacher, who wants to give meaning to the learning of his future students, because in the speech of these perceives the necessities that these student have to know other methodologies of teaching / learning in substitution of the Cartesian mechanical methodology that they coexisted during all basic and middle formation. Therefore this work began discussing about the evolution of the scientific method, later about the CTS Trend, the didactic book proposes and the Mathematical Modeling. After that, the experimental activities using theses methodologies proposals. In this direction, is perceptive that these students, future teachers, will former pupils prepared to exert your citizenship, with the aid of the CTS Trend and Mathematical Modeling.